2006
DOI: 10.1124/mol.105.020578
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Mechanism for the Anti-Inflammatory Effect of Taurine-Conjugated 5-Aminosalicylic Acid in Inflamed Colon

Abstract: In previous reports, a novel colon-specific prodrug, 5-aminosalicyltaurine (5-ASA-Tau) administered orally, is successfully delivered to and liberates 5-aminosalicylic acid (5-ASA) and taurine in the inflamed large intestine of rats. Furthermore, the prodrug ameliorates the 2,4,6-trinitrobenzene-sulfonic acid-induced colitis, and taurine acts not only as a carrier but also as an active therapeutic agent. In this study, we investigated the anti-inflammatory properties of the prodrug at a molecular level. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…Furthermore, another study using a taurine derivative (taurine chloramines) demonstrated that taurine was able to regulate the synthesis of proinflammatory cytokines, thus suggesting that taurine may have a role in the initiation and propagation of the immune response (63). In addition, a previous study reported that the levels of IL-2 and IFN-γ were markedly elevated following treatment with curcumin and taurine, and were approximately equal to the control untreated levels (64).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another study using a taurine derivative (taurine chloramines) demonstrated that taurine was able to regulate the synthesis of proinflammatory cytokines, thus suggesting that taurine may have a role in the initiation and propagation of the immune response (63). In addition, a previous study reported that the levels of IL-2 and IFN-γ were markedly elevated following treatment with curcumin and taurine, and were approximately equal to the control untreated levels (64).…”
Section: Discussionmentioning
confidence: 99%
“…79 In addition, in vivo and in vitro studies evaluated the effects of a prodrug 5-aminosalicyltaurine which had a protective role in TNBS-induced colitis 80 and limited inflammatory response in cultured cells. 81 This prodrug appears to be more effective than the reference drug 5-ASA. 80 …”
Section: Other Amino Acidsmentioning
confidence: 97%
“…These results are similar to the results described by Fiorucci et al [38] . Furthermore, Kim et al showed that 5-ASA attenuated TNF-dependent NF-kB activation, which may be critical during intestinal inflammation [39] . Considering these results, and the strong correlation between the intestinal levels of IFN-γ and TNF-α and the amount of EB, we hypothesize that balsalazine protects the intestinal mucosal barrier partly by inhibiting the proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%